PENGARUH PRODUK AR RAHN DAN PRODUK MULIA TERHADAP PENDAPATAN PT. PEGADAIAN (PERSERO) SYARIAH - Dini Fitrianti (Jurnal Akrab Juara, 2019)
This study aims to investigate the influence of ar rahn product and noble product to revenue PT. Pegadaian (Persero) Syariah. This study uses data that PT. Pegadaian (Persero) located on Jalan Kramat Raya 162, Central Jakarta. The study was conducted in December 2014 until January 2015. While the method of data multiple linier regression analysis. Results in partial test (t test) obtained that ar rahn product effect on revenue and noble product has no effect on revenue. Where the error rate used is 5 % or 0.05 at significant level of 95%.